North American thinking and the process of incorporating environmental issues in social sciences - Potiara Castro, Carlos; da Costa Ferreira, Leila (Departamento de Estudos Latino-Americanos - ELA, 2014)
This paper aims to discuss the foundation upon which the first authors who worked with environmental issues in the social sciences based themselves. It raises the hypothesis that these foundations strongly identify with the tradition of American thinking in both social sciences and philosophy. It describes briefly the development of the field of environment and society studies, with a primary focus on subjects covered in United States and in Brazil.